2023
DOI: 10.1155/2023/8974960
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Attenuates Hepatic Oxidative Stress, Inflammation, and Apoptosis in Streptozotocin-Induced Diabetic Mice by Modulating the Wnt/β-Catenin Signaling Pathway

Abstract: Liraglutide has been extensively applied in the treatment of type 2 diabetes mellitus and also has hepatoprotective effects. However, the role of liraglutide treatment on liver injury in a mouse model of type 1 diabetes mellitus (T1DM) induced by streptozotocin (STZ) and its underlying mechanisms remain to be elucidated. In the present study, diabetes was initiated in experimental animals by single-dose intraperitoneal inoculation of STZ. Forty female C57BL/6J mice were equally assigned into five groups: diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“… 6 , 32 Histological variations were observed in the liver tissues of STZ-induced mice, rats, and dogs, such as hepatic steatosis, apoptosis, hepatocytes with intracellular lipid droplets, and inflammation. 6 , 8 , 32 We observed that steatohepatitis, fibrosis, and apoptosis were increased in the T1DM group, consistent with previous findings. 8 , 32 Poor glycemic control elevated levels of serum triglycerides, VLDL, and LDL, and decreased HDL-C levels in both patients and experimental animals with diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“… 6 , 32 Histological variations were observed in the liver tissues of STZ-induced mice, rats, and dogs, such as hepatic steatosis, apoptosis, hepatocytes with intracellular lipid droplets, and inflammation. 6 , 8 , 32 We observed that steatohepatitis, fibrosis, and apoptosis were increased in the T1DM group, consistent with previous findings. 8 , 32 Poor glycemic control elevated levels of serum triglycerides, VLDL, and LDL, and decreased HDL-C levels in both patients and experimental animals with diabetes.…”
Section: Discussionsupporting
confidence: 91%
“… 6 , 8 , 32 We observed that steatohepatitis, fibrosis, and apoptosis were increased in the T1DM group, consistent with previous findings. 8 , 32 Poor glycemic control elevated levels of serum triglycerides, VLDL, and LDL, and decreased HDL-C levels in both patients and experimental animals with diabetes. 17 , 33 - 36 In our study, we found that diabetes resulted in elevated the levels of TC, TG, LDL-C, and decreased HDL-C level, which is line with previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, it has also been proven to regulate the function of pancreatic organs and play a role in pancreatic beta cells and glucose-stimulated insulin secretion ( 130 ). The Wnt pathway may also play a role in more aspects, but the role and mechanism of this pathway still need to be studied.…”
Section: Mechanismmentioning
confidence: 99%